Discovery of mitochondria-targeting berberine derivatives as the inhibitors of proliferation, invasion and migration against rat C6 and human U87 glioma cells. Issue 1 (20th October 2014) - Fu, Shengnan; Xie, Yanqi; Tuo, Jue; Wang, Yalong; Zhu, Wenbo; Wu, Sihan; Yan, Guangmei; Hu, Haiyan
Abstract : This research aims to synthesize lipophilic berberine derivatives and evaluate their antiglioma effects on C6 and U87 cells. Abstract : This research aims to synthesize lipophilic berberine derivatives and evaluate their antiglioma effects on C6 and U87 cells. The introduction of substituents with various carbon chain lengths on C-13- or C-9-O-position of the berberine scaffold led to the discovery of several potent inhibitors against glioblastoma cells. Derivatives substituted with the carbon chains of moderate length (twelve carbons) displayed improved lipophilicity and the strongest inhibitory effects. Several compounds presented dose-dependent repression against proliferation (IC50, 1.12–6.12 μM) and blocked migration and invasion by over 60% at lower dose levels. Furthermore, preliminary research about the underlying mechanism for the enhanced antiglioma ability indicated that these analogues preferentially localized into mitochondria, inducing the up-regulation of ROS production. Overall, these compounds represent promising candidates to combat glioblastoma and highlight new insight into the antiglioma therapy through interaction with mitochondria.